Purification of Human Plasminogen - Roberts, P. S; Burkat, R. K (Thrombosis and Haemostasis, 1967)
Highly purified Kline-type plasminogen was obtained from Fraction III of human blood plasma by acid-salt extraction and precipitation procedures. Fraction III was washed with 1 M NaCl at pH 2 to remove interfering substances. Plasminogen was then extracted with 0.2 M NaCl at pH 2 and was further purified by precipitating it at pH 5.8 in the absence and in the presence of 0.1 M lysine. Highly purified material, although in varying yield, was obtained from all 3 lots of Fraction III (dried powder) and the 1 lot of Fraction III (frozen paste) used.